Meta-Analytical Validity of the Social Entrepreneurship Inventory: A Study of Random Effect Sizes (Global Journal of Management and Business Research, 2019)
The meta-analytic validity understood as the evidence of homogeneity demonstrated through parameters that measure the normal distribution, sum of total effects and proportions of differences between the studies consulted was the objective of the present work. A meta-analytical study was conducted with a selection of sources indexed to international repositories, considering the publication period from 2015 to 2019. The meta-analytical threshold of predictive confidence was established, although the research design limited the findings of heterogeneity to the study sample, suggesting the extension of the work towards indexed sources and publications prior to that observed.
Keywords: migration; entrepreneurship; meta-analysis; confidence interval; homogeneity